Pemetaan Global Music Value Chain ADOR Entertainment: Studi Kasus Album "Supernatural" NewJeans - Hidayati, Anugrah Nurul; Purbantina, Adiasri Putri (Journal of Music Science, Technology, and Industry, 2025)
Purpose: This study aims to describe the application of the Global Creative Music Chain concept by ADOR Entertainment on the NewJeans album “Supernatural”, which involves cross-border contributions and interactions in managing the global value chain in the music industry. Research methods: The method used is descriptive with a qualitative approach, which uses data collection techniques from literature studies with data sources from the album “Supernatural” by NewJeans, the official websites of HYBE Corporation and ADOR Entertainment, mass media articles and news, official social media from NewJeans, as well as related sources related to the research topic. Results and discussion: The results showed cross-border interaction at all stages and activities of the album “Supernatural” production by NewJeans, both in core and support functions. Implication: This research contributes novelty to music studies by examining the global music value chain, which has not been widely done.